Assessment of Over-the-Counter (OTC) Drug Usage Patterns and Awareness among College Students - Khanam, Simran; Moin, Saman; Yadav, Rajesh (Journal of Pharmacy Practice and Community Medicine, 2026)
Objectives: The present study was conducted to assess the Knowledge, Attitude, and Practice (KAP) regarding the use of Over-the-Counter (OTC) drugs among 101 participants. Materials and Methods: A cross-sectional survey was carried out using a structured questionnaire. Participants. The majority of participants belonged to the 21-23 years age group (38.6%), with a mean age of 21.84 years. Results: The results showed that 83.2% of participants reported using OTC medicines, with most using them rarely (67.3%). - Fever (49.5%) and headache were the most common conditions for OTC drug use, and painkillers (64.4%) were the most frequently used medications. Convenience (39.6%) and avoiding doctor visits (29.7%) were the primary reasons for use. Awareness regarding OTC drugs was high, with 97% of participants demonstrating good knowledge. However, practice was only moderate in 62.4% of participants, and 66.3% exhibited a negative attitude toward OTC drug use. The mean scores were 5.79±0.47 for awareness, 2.18±0.61 for practice, and 1.10±1.03 for attitude. The Chi-square test showed no significant association between awareness and practice (p=0.839). Conclusion: The study concludes that despite high awareness, safe practices are not consistently followed, highlighting the need for educational interventions.
Keywords: Analgesics; Antihistamines; Antipyretics; Awareness; College students; Healthcare; Behavior; Over-the-Counter Drugs; Rational Drug Use; Self-Medication; Usage Patterns